2020
DOI: 10.1155/2020/4918239
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin Exerts Protective Effects against Ankylosing Spondylitis by Regulating NF-κB-TH17/JAK2/STAT3 Signaling and Oxidative Stress

Abstract: Background. Ankylosing spondylitis (AS) is a chronic inflammatory disease characterized by sacroiliitis and spinal rigidity of the axial joints. The role of oxidative stress and increased proinflammatory cytokines is well documented in AS pathogenesis. Punicalagin (2,3-hexahydroxydiphenoyl-gallagyl-D-glucose), an ellagitannin widely present in pomegranates, is found to exhibit potent anti-inflammatory, antiproliferative, and antioxidative effects. The present study was undertaken to investigate the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
2
19
0
2
Order By: Relevance
“… 32 Another study also suggested the punicalagin exerted a protective role in ankylosing spondylitis via reducing oxidative stress and the production of inflammation cytokines by the Th17 cells and the IL-17A/IL-23 axis. 33 In our findings, we demonstrated that the treatments of punicalagin significantly down-regulated the expression and secretion of IL-1β, IL-6, IL-8 and IL-17A. These findings make punicalagin a promising target for anti-inflammatory therapies of RA.…”
Section: Discussionsupporting
confidence: 61%
“… 32 Another study also suggested the punicalagin exerted a protective role in ankylosing spondylitis via reducing oxidative stress and the production of inflammation cytokines by the Th17 cells and the IL-17A/IL-23 axis. 33 In our findings, we demonstrated that the treatments of punicalagin significantly down-regulated the expression and secretion of IL-1β, IL-6, IL-8 and IL-17A. These findings make punicalagin a promising target for anti-inflammatory therapies of RA.…”
Section: Discussionsupporting
confidence: 61%
“…Punicalagin (PUN) is a polyphenol isolated from pomegranate and displays a variety of pharmacological activities, of which antioxidant and anti-inflammatory are the most important [125,126]. It seems that antioxidant activity of PUN is mediated via its impact on Nrf2 signaling pathway.…”
Section: Natural Compounds In Ameliorating Doxorubicin-mediated Toxicitymentioning
confidence: 99%
“…The activated JAK/STAT3 signaling pathway and increased levels of ROS both were found to be involved in pathological formation of ankylosing spondylitis [ 78 , 79 ]. In ankylosing the spondylitis mouse model, ROS and malonaldehyde levels were increased, and punicalagin treatment significantly reduced ROS and malonaldehyde levels, and effectively improved antioxidant status in ankylosing spondylitis BALB/c mice [ 80 ]. This effect may be conducted by regulating the major pathway of inflammatory response JAK/STAT3 signaling [ 80 ].…”
Section: Role Of Punicalagin In Inflammation-associated Diseasesmentioning
confidence: 99%
“…In ankylosing the spondylitis mouse model, ROS and malonaldehyde levels were increased, and punicalagin treatment significantly reduced ROS and malonaldehyde levels, and effectively improved antioxidant status in ankylosing spondylitis BALB/c mice [ 80 ]. This effect may be conducted by regulating the major pathway of inflammatory response JAK/STAT3 signaling [ 80 ]. In other research, punicalagin (250 mg/kg) pretreated with concanavalin A-induced autoimmune hepatitis mice down-regulated the levels of IL-6, TNF-α and IFN-γ, and reduced the infiltration of activated CD4 + and CD8 + T cells in liver [ 81 ].…”
Section: Role Of Punicalagin In Inflammation-associated Diseasesmentioning
confidence: 99%